On modeling integrated design environments - Hübel, Christoph; Ruland, Detlev; Siepmann, Ernst (Euro-DAC '92, European Design Automation Conference : Euro-VHDL '92, Congress Centrum Hamburg, Hamburg, Germany, September 7-10, 1992, 1992)
Most existing approaches towards modeling design methodologies concentrate on modeling of design flows and design tools. Only a few of them consider the relationships between design methodology and design object modeling. Our approach towards modeling the heterogeneous aspects of design environments is based on a paradigm of separation and integration yielding an adequate, well structured, non-redundant, and integrated design model for generic design environments. The design model consists of five partial models: (1) design flow model, (2) design tool model, (3) design structure model, (4) design object model, and (5) design subject model. The design structure model is introduced for modeling on a higher level of abstraction exactly those aspects of design objects which are necessary for design methodology management. The applied concept is called design object abstraction.